2002
DOI: 10.3386/w9246
|View full text |Cite
|
Sign up to set email alerts
|

Information Content of Equity Analyst Reports

Abstract: This paper investigates the market reaction to the information released in security analyst reports. It shows that the market reacts significantly and positively to changes in recommendation levels, earnings forecasts, and price targets. While changes in price targets and earnings forecasts both provide information to the market, revisions in price targets have a larger and more significant impact than comparable revisions in earnings forecasts. The text of the report is also a significant source of informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
393
5
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(430 citation statements)
references
References 14 publications
24
393
5
8
Order By: Relevance
“…Several relatively more recent studies have examined the informativeness of analyst reports. For example, Kothari, Li Asquith et al (2005) tested their specific information components (contents). In contrast to these studies, which focus on what information is communicated, this paper studies analyst reports from a different angle, using different tools, and focuses on how the information is communicated (i.e.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Several relatively more recent studies have examined the informativeness of analyst reports. For example, Kothari, Li Asquith et al (2005) tested their specific information components (contents). In contrast to these studies, which focus on what information is communicated, this paper studies analyst reports from a different angle, using different tools, and focuses on how the information is communicated (i.e.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Asquith et al (2005) This is the Pre-Published Version suggested that analyst reports provide useful information to investors whereas Li (2008) provided empirical evidence of the importance of readability of annual reports, and posited that studying the readability of analyst reports allows us to understand analyst reports from a different angle. Li et al (2011) further extend the studies on financial reports' readability by studying the association between readability of 10K filings and analyst behaviors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…• %ܶܲ i is the percentage of the target prices hit by the actual security prices over the next 12 month (Asquith et al (2005)). …”
Section: Assocation Between Ppas' Quality and Change In Forecasts' Acmentioning
confidence: 99%
“…It is believed that analysts have better knowledge of a firm's fundamental information and that this knowledge therefore reduces the information asymmetry between firms and investors. Studies have pointed out that analysts' earnings forecasts provide investors with valuable information, for example, Asquith et al (2005) found that analysts' reports provide new information and that the market reacts to earnings forecast revisions, recommendation revisions, and price target revisions. Franket et al (2006) also find bad news forecast revisions have a greater impact on price than positive forecast revisions.…”
Section: Introductionmentioning
confidence: 99%